2020
DOI: 10.3390/genes11111368
|View full text |Cite
|
Sign up to set email alerts
|

SWI/SNF Alterations in Squamous Bladder Cancers

Abstract: Dysfunction of the SWI/SNF complex has been observed in various cancers including urothelial carcinomas. However, the clinical impact of the SWI/SNF complex in squamous-differentiated bladder cancers (sq-BLCA) remains unclear. Therefore, we aimed to analyze potential expression loss and genetic alterations of (putative) key components of the SWI/SNF complex considering the co-occurrence of genetic driver mutations and PD-L1 expression as indicators for therapeutic implications. Assessment of ARID1A, SMARCA2, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Squamous differentiation is observed in 25% of human endometrial cancer and was recently associated with disease recurrence, and it has been observed in mouse models [99][100][101]. ARID1A and SWI/SNF mutations have been shown to promote carcinogenesis of various squamous tumor types [102,103]. We observed that ARID1A mutant UCEC tumors have higher TP63 expression than TP53 mutant tumors.…”
Section: Plos Geneticsmentioning
confidence: 57%
“…Squamous differentiation is observed in 25% of human endometrial cancer and was recently associated with disease recurrence, and it has been observed in mouse models [99][100][101]. ARID1A and SWI/SNF mutations have been shown to promote carcinogenesis of various squamous tumor types [102,103]. We observed that ARID1A mutant UCEC tumors have higher TP63 expression than TP53 mutant tumors.…”
Section: Plos Geneticsmentioning
confidence: 57%
“…In contrast, the opposite results were observed when FBXO28 was knocked down. Mutations and loss of expression of the SWI/SNF complex and its subunits are found in various tumors, such as endometrial cancer [ 36 ], esophageal adenocarcinoma [ 37 ], lung cancer [ 38 ], thyroid cancer [ 39 ], and bladder cancer [ 40 ]. Tsuda et al [ 41 ] showed that SWI/SNF subunits and their downstream pathways are potential therapeutic targets in PC.…”
Section: Discussionmentioning
confidence: 99%